新冠疫情背景下中国汉语新词语探究 - 何, 芝垒 (2023)
语言既是交际工具，也是社会现象的反映。词汇随着社会新事物、新现象、新概念的出现而诞生，是语言三要素（语音、词汇、语法）中最具活力的。新冠疫情暴发后，衍生出许多疫情新词语广泛使用于生活中，承担着科普知识、传达信息、表达情感与思想等重要作用，对当时的社会生活产生了极大的影响。从语言学的角度来说，要阐释语言的动态变化，就需要对词汇的变动进行记录和分析。从词汇系统的发展历程来看，疫情新词语诞生的时间不长，经观察发现，在这些疫情新词语中，存在不符合汉语造词结构和造词规律，以及带有歧视性色彩现象。截至 2023 年 3 月，中国内地关于疫情新词语的研究有学位论文1 篇，期刊论文9篇，这些研究成果对疫情新词的定义界定、造词方式、产生原因等都未做深入探讨。本论文以中国内地 2019 年 12 月至 2022 年 12 月产生的疫情新词语为研究对象，通过对比分析法、数据统计与图表分析法、宏观分析与微观探究相结合法，综合了词义学、语义学、语法学、修辞学、语用学和社会语言学的理论，对疫情新词语的定义界定、领域分布、造词方式、语用功能以及产生的原因展开探究。研究结果得出：来自社会生活领域的疫情新词语占比最多，反映了疫情之下民众的生活状态。疫情新词语的造词方式有词语模、修辞格、旧词新义、方言词、缩略，以及“数字、字母、符号和汉字组合”六种；语用功能体现在描述疫情发展状况、聚焦疫情热点事件、缓解疫情心理压力三个方面；产生的原因有社会生活的变化、语言自身的发展，以及互联网媒体的推动。Language is not only a tool of communication, but also a reflection of social phenomena. Vocabulary is born with the emergence of new social things, newphenomenaand new concepts, and is the most dynamic among the three elements of language(phonetics, vocabulary and grammar). After the outbreak of the novel coronavirus, many new epidemic words were derivedand widely used in daily life, assuming the important role of popular science knowledge, conveying information, expressing emotions and thoughts, and having a great impact onsocial life at that time. From the perspective of linguistics, to explain the dynamic changesof language, it is necessary to record and analyze the changes of vocabulary. From the perspective of the development of the vocabulary system, the emergence of epidemic new words has not been a long time. After observation, it is found that amongthese epidemic new words, there are discriminatory phenomena that do not conformtothestructure and rules of Chinese word making. As of March 2023, there are 1 academic dissertation and 9 journal papers on COVID-19 neologisms in mainland China, and theseresearch results have not made in-depth discussions on the definition, coinage and causes of COVID-19 neologisms. This paper takes the epidemic neologism produced in mainland China fromDecember 2019 to December 2022 as the research object, and combines the theories of semantic science, semantics, grammatology, rhetoric, pragmatics and sociolinguistics through comparative analysis, data statistics and chart analysis, macro analysis and microinvestigation. This paper probes into the definition, field distribution, ways of word making, pragmatic functions and causes of new epidemic words. The results showed that the proportion of epidemic new words fromthe field of social life was the largest, reflecting the people's living conditions under the epidemic. There are six ways of making new epidemic words: word model, figure of speech, newmeaning of old words, dialect words, contractions, and "combination of numbers, letters, symbols and Chinese characters". The pragmatic function is embodied in describing the development of the epidemic situation, focusing on the hot events of the epidemic, andrelieving the psychological pressure of the epidemic. The reasons are the changes of social life, the development of language itself, and the promotion of Internet media.